(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Already in the second decade of the 21st century, the pace of industry and production in the history of mankind is surpassing the records of previous times. Introducing new types of products and services to the market and their popularization, Internet and social networks becoming an integral part of people’s lives are among the specific development trends of the modern lifestyle.